Analisis Semantik terhadap Makna Nilai-nilai Religiusitas dalam Dialog Film Ayat-Ayat Cinta - Firdaus, Dadan; Asmaradana, Lintang; Muharomi, M Zidan; Hanafi, Muhammad Akmal Lukman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the semantic meanings of religiosity represented in the dialogues of the film Ayat-Ayat Cinta. Using a descriptive qualitative approach, the research applies Geoffrey Leech’s semantic theory, focusing on conceptual, connotative, affective, and social meanings. The data consist of eleven dialogue excerpts containing Islamic values spoken by the main characters. Data were gathered through observation, transcription, and note-taking, and subsequently analyzed by categorizing and interpreting their meanings according to semantic categories. The findings show that religiosity in the film is reflected through themes such as destiny, marriage, kindness, social ethics, Islamic teachings, ta’aruf, worship, patience, and trust in God. Moreover, the film serves not merely as entertainment but also as a means of Islamic preaching, promoting faith, morality, tolerance, and social responsibility. These findings demonstrate that semantic analysis helps reveal how religious meanings are constructed and communicated through language in audiovisual media .